KESIAPAN MENIKAH DAN PEMENUHAN TUGAS KELUARGA PADA KELUARGA DENGAN ANAK USIA PRASEKOLAH - Sunarti, Euis; Simanjuntak, Megawati; Rahmatin, Ine; Dianeswari, Restystika (Jurnal Ilmu Keluarga dan Konsumen, 2012)
The aimed of this research was to analyze the difference, correlation, and influence of marital readiness, basic task, crisis task, and development task fulfillment of preschool families in Bubulak Village, Bogor District, West Java Province. Ninety families with preschool-aged children were chosen by simple random sampling. Data were collected by interviews and analyzed by descriptive, Pearson correlation, and multiple linear regression test. The results showed that wife marital readiness lower compared with husband marital readiness. Husband and wife marital readiness correlated with family tasks fulfillment. Husband and wife marital readiness also had a significant effect on family developmental tasks. Family developmental tasks and wife marital readiness influenced on child development. Husband and wife marital readiness also have a significant effect on the family crisis task. Based on this, policy makers were expected to increase family’s strength and empowerment, especially in family with school-aged children.